Supercritical fluids for the isolation and formulation of bioactive substances: Superkritični fluidi za izolacijo in formulacijo bioaktivnih snovi - Knez Marevci, Maša; Andrina Kravanja, Katja; Knez, Željko (Acta Medico-Biotechnica, 2024)
Technologies involving sub- and supercritical fluids offer the possibility to obtain new products with special characteristics, which are especially needed in the pharmaceutical industry. The use of sub- or supercritical fluids for processing can also address legal limits for solvent residues and restrictions on the use of conventional solvents, while enabling new processes that are environmentally friendly and sustainable. Extraction of substances from plant materials, their in situ formulation in products with specific properties, particle formation, foaming, deposition, and sterilization have attracted much attention among the applications of supercritical fluids. This short overview reports the current status and expected future developments of research into sub- and supercritical fluid technologies.